Building Creativity And Imagination In Early Childhood Through Picture Story Books - Silaban, Ronita lena sari; Sofania Magdalena Siadari; Butar Butar, Mei Lastri E.F. (PRODI PKAUD, IAKN TARUTUNG, 2024)
Children are honest learners who express their feelings and imagination. Related to imagination, basically all children are creative where according to George & Zhou (in Ashkanasy & Rowe, 2008) creativity is a product of ideas or solutions that are new and useful. Building creativity and imagination in early childhood is a crucial component in their cognitive, emotional and social development. Picture storybooks are one of the most effective educational tools in stimulating these two aspects. This study aims to examine how the use of picture storybooks can develop creativity and imagination in early childhood, as well as the best method of presenting them. Through literature review and participatory observation, this research highlights the important role of illustrations in picture storybooks. Attractive and colourful images not only capture children's attention, but also help them understand and internalize the story better. These images provide a visual jolt that can enrich children's imagination, encouraging them to imagine worlds and characters that are not limited to their real-life experiences. This process helps children develop creative thinking skills, where they learn to think outside the real boundaries and find innovative solutions to various situations. This research also emphasizes the importance of choosing the right picture storybooks. The books selected should be appropriate for the child's age, interests and developmental level. Books with stories that promote positive values, such as cooperation, honesty and courage, can have a positive impact on children's ethical and social development. Keywords: Creativity and Children's, Imagination, Early childhood, Story book with picture